TOF‐SIMS VG Ionex IX23LS: upgrade and application for the urinary stones analysis. (4th May 2012) - Ghumman, C. A. A.; Moutinho, A. M. C.; Santos, A.; Tolstogouzov, A.; Teodoro, O. M. N. D.
<x xml:space="preserve">Abstract</x> TOF‐SIMS VG Ionex IX23LS with upgraded data acquisition and control system was used to study the real urinary stones along with calcium oxalate (COX) and four different calcium phosphate (CP) references. Reliable phase identification of CPs was achieved in the positive SIMS mode on basis of the PO+/POH+ and CaPO2+/Ca2O+ peak ratios. In real urinary stones, pure COX was distinguished from calcium phosphates with confidence via the presence of its characteristic ion peaks. We also quantified the calcium phosphate in the human calculi containing calcium oxalate as major or minor component, which is of a great interest for medical community. Copyright © 2012 John Wiley & Sons, Ltd.